2021
DOI: 10.1016/j.xops.2021.100069
|View full text |Cite
|
Sign up to set email alerts
|

Federated Learning for Microvasculature Segmentation and Diabetic Retinopathy Classification of OCT Data

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…This approach has been successfully implemented in the context of retinal microvasculature segmentation and referable diabetic retinopathy detection on optical coherence tomography (OCT) and OCT angiography images. The authors demonstrated that a federated learning approach achieved similar results as a traditional centralized learning approach ( 25 ). Similarly, instead of transferring data to train a DL model, the model itself can be “brought” to the data for retraining.…”
Section: Discussionmentioning
confidence: 96%
“…This approach has been successfully implemented in the context of retinal microvasculature segmentation and referable diabetic retinopathy detection on optical coherence tomography (OCT) and OCT angiography images. The authors demonstrated that a federated learning approach achieved similar results as a traditional centralized learning approach ( 25 ). Similarly, instead of transferring data to train a DL model, the model itself can be “brought” to the data for retraining.…”
Section: Discussionmentioning
confidence: 96%
“…In their work, Bercea et al (2021) proposed a framework for federated unsupervised brain anomaly segmentation. In their work, Lo et al (2021) showed that a federated learning model could achieve similar results as models trained on fully centralized data for microvasculature segmentation. While these methods mainly focus on regular 2D segmentation tasks for grid images, this work, in contrast, investigates the more challenging 3D tooth segmentation task over complicated and heterogeneous geometrical medical data.…”
Section: Federated Learning For Medical Image Segmentationmentioning
confidence: 97%
“…Additionally, in [ 116 ], the authors evaluated the effectiveness of federated neural network-based retinal microvasculature segmentation and classification of referable diabetic retinopathy (RDR) using optical coherence tomography (OCT) and OCT angiography (OCTA). For this purpose, several datasets were used, including SFU prototype swept-source OCTA, RTVue XR Avanti (OptoVue, Inc.), Angioplex (Carl Zeiss Meditec), and PLEX Elite 9000 (Carl Zeiss Meditec).…”
Section: Federated Learning In Actionmentioning
confidence: 99%